2001
DOI: 10.1063/1.1344885
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electric polarizability in metal C60 compounds: Formation of a sodium droplet on C60

Abstract: Articles you may be interested inElectric dipole (hyper)polarizabilities of spatially confined LiH molecule J. Chem. Phys. 137, 094307 (2012); 10.1063/1.4748144 Thermally induced polarizabilities and dipole moments of small tin clusters J. Chem. Phys. 136, 134320 (2012); 10.1063/1.3699071Calculation of electric dipole (hyper)polarizabilities by long-range-correction scheme in density functional theory: A systematic assessment for polydiacetylene and polybutatriene oligomers A systematic study of basis set, ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…In these early works, they found for lithium certain "magic numbers" which can only arise from an homogeneous distribution of twelve Li atoms on the top of the pentagonal faces of fullerene. Some other elements were found to form clusters above a certain concentration, or to form other non-homogeneous distributions on the surface [18,19,20,21,22,23]. This behavior is detrimental for hydrogen adsorption, because the clustering of the metal atoms on the surface of C 60 reduces the active adsorption sites for H 2 [24].…”
Section: Introductionmentioning
confidence: 99%
“…In these early works, they found for lithium certain "magic numbers" which can only arise from an homogeneous distribution of twelve Li atoms on the top of the pentagonal faces of fullerene. Some other elements were found to form clusters above a certain concentration, or to form other non-homogeneous distributions on the surface [18,19,20,21,22,23]. This behavior is detrimental for hydrogen adsorption, because the clustering of the metal atoms on the surface of C 60 reduces the active adsorption sites for H 2 [24].…”
Section: Introductionmentioning
confidence: 99%
“…Here, the major forces stabilizing the complex were vdW interactions and C–H···π contacts between the −H of −CH 3 groups of the ligands and the π-system of C 60 . Moreover, it is well-known that metal clusters can also bind to fullerene surfaces . From Figure , it is clear that there were strong contacts between the Ag atoms of the cluster and C 60 , which contributed ion-induced dipole interactions to the overall stabilization of the complex.…”
Section: Resultsmentioning
confidence: 93%
“…Although not discussed in that work, it seems likely that atomic cesium will be pulled into the droplet once a C 60 A n aggregate has formed because the electric polarizability of C 60 A n is an order of magnitude larger than that of C 60 . 47 , 48 If a Cs dimer but not a Cs atom would be pulled into a droplet containing a C 60 Cs n aggregate, an interesting odd–even effect would appear where C 60 -doped helium droplets containing n Cs atoms would consist of solvated (C 60 ) m Cs n if n is even but solvated (C 60 ) m Cs n –1 plus a Cs atom on the surface if n is odd.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers at the University of Lyon have measured the electric susceptibility of neutral C 60 Na n in a molecular beam deflection experiment. ,, Strong deflection was attributed to complete segregation, i.e., formation of a single sodium droplet for all values of n . In later work though, supported by DFT studies, it was concluded that the first 8 sodium atoms spread uniformly over the C 60 surface. ,, In a subsequent DFT study Rabilloud concluded that up to 12 sodium atoms prefer to form distinct tetrahedral islands …”
Section: Discussionmentioning
confidence: 99%